Activation of the mouse primary visual cortex by medial prefrontal subregion stimulation is not mediated by cholinergic basalo-cortical projections - Nguyen, Hoang Nam; Huppé-Gourgues, Frédéric; Vaucher, Elvire (Frontiers in Systems Neuroscience, 2015)
The medial prefrontal cortex (mPFC) exerts top-down control of primary visual cortex (V1) activity. As there is no direct neuronal projection from mPFC to V1, this functional connection may use an indirect route, i.e., via basalo-cortical cholinergic projections. The cholinergic projections to V1 originate from neurons in the horizontal limb of the diagonal band of Broca (HDB), which receive neuronal projections from the ventral part of the mPFC, composed of prelimbic (PrL) and infralimbic cortices (IL). Therefore, the objective of this study was to determine whether electrical stimulation of mice mPFC subregions activate 1) V1 neurons and 2) HDB cholinergic neurons, suggesting that the HDB serves as a relay point in the mPFC-V1 interaction. Neuronal activation was quantified using c-Fos immunocytochemistry or thallium autometallography for each V1 layer using automated particle analysis tools and optical density measurement. Stimulation of IL and PrL induced significantly higher c-Fos expression or thallium labelling in layers II/III and V of V1 in the stimulated hemisphere only. A HDB cholinergic neuron-specific lesion by saporin administration reduced IL-induced c-Fos expression in layers II/III of V1 but not in layer V. However, there was no c-Fos expression or thallium labelling in the HDB neurons, suggesting that this area was not activated by IL stimulation. Stimulation of another mPFC subarea, the anterior cingulate cortex (AC), which is involved in attention and receives input from V1, activated neither V1 nor HDB. The present results indicate that IL and PrL, but not AC, stimulation activates V1 with the minor involvement of the HDB cholinergic projections. These results suggest a functional link between the ventral mPFC and V1, but this function is only marginally supported by HDB cholinergic neurons and may involve other brain regions.